Incidence and Occurrence of Latent Ralstonia solanacearum Infection in Seed Potato from Farmer Seed Grower Cooperatives in Southern and Central Ethiopia - Tessema, L.; Seid, E.; Giorgis, G.W.; Sharma, K.; Workie, M.; Negash, K.; Misganaw, A.; Abebe, T. (Springer, 2022)
Bacterial wilt (BW) of potato caused by Ralstonia solanacearum (Rs) has been and continues to be a devastating disease of potato and related crops worldwide particularly vegetatively propagated ones. In Ethiopia, potato BW has spread to many areas due to absence of an effective seed potato system with fair seed certification, disease monitoring, and containment. Seed potato in Ethiopia is generally visually inspected resulting in failure to detect Rs in latently infected stock assumed clean by visual assessments. Consequently, a study was conducted to assess the extent of Rs latent infection in seed potato in major seed potato producing cooperatives in southern, southwestern, and central highlands of Ethiopia using Nitrocellulose membrane ELISA. A total of 41,600 tuber samples were collected between 2015 and 2016 from 121 fields of 57 registered seed potato grower cooperatives representing 107.05 ha distributed in 14 districts. Results of latent Rs infection indexing indicated that 58.3% of analysed samples were infected, more so during the March-June 2015 cropping season. The prevalence of latent infection was not significantly (P >= 0.05) influenced by potato variety or altitude at which the sample was collected but occurred randomly across altitude. The disease was evident even in samples collected at altitudes as high as 3000 m above sea level. Two samples collected at more than 3000 m above sea level were clean. However, these were too few to assume there is no BW above this altitude. In the absence of a reliable and sustainable seed potato testing for latent infection, farmers seed group cooperatives (FSGCs) who are the main producers of seed potato in Ethiopia as quality declared seed (QDS) will continue to disseminate Rs even in seed produced at extremely high altitude agro-ecologies. Consequently, it is recommended that QDS from FSGCs should be subjected to mandatory latent Rs infection indexing before they can be distributed as trusted potato planting stock despite the cost that would be involved. This should be complemented with BW infection containment effort combining biological, agronomic, policy, and social contexts.